1996
DOI: 10.1007/s002689900117
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Retroperitoneoscopy as a New Minimally Invasive Approach for Adrenalectomy: Results of 30 Adrenalectomies in 27 Patients

Abstract: Posterior retroperitoneoscopic adrenalectomy is a new minimally invasive method. It represents an alternative to conventional open procedures and laparoscopic techniques. Between July 1994 and November 1995 a total of 30 retroperitoneoscopic adrenalectomies were performed on 27 patients. In 24 patients, unilateral tumors were seen (size 1-7 cm): seven Cushing adenomas, five Conn adenomas, seven pheochromocytomas, four hormonally inactive tumors, one cyst. Three patients suffered from Cushing syndrome with bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
138
0
20

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(179 citation statements)
references
References 24 publications
12
138
0
20
Order By: Relevance
“…The irritation of the subcostal nerve in our study was comparable to the subcostal nerve irritation described in the literature [8,13,18,19].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The irritation of the subcostal nerve in our study was comparable to the subcostal nerve irritation described in the literature [8,13,18,19].…”
Section: Discussionsupporting
confidence: 73%
“…In the published literature the operation time seems to be shorter in the retroperitoneal approach compared to other techniques. Nevertheless, this result can only be reached by an experienced surgeon and after a certain learning curve [18]. Moreover, the published data about retroperitoneoscopic adrenalectomy show a shorter operation time for the dorsal approach [3,10,12,14,17,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BAETS 2012 audit showed that only 86 of 1359 patients (6%) who underwent adrenalectomy had a bilateral operation. 4 Laparoscopic unilateral adrenalectomy was initially reported in 1992 5 and within the last two decades has become the standard of care for benign adrenal tumours. It has been widely adopted because of its decreased morbidity and perioperative complications compared with the open approach.…”
Section: Introductionmentioning
confidence: 99%
“…Retroperitoneoscopic adrenalectomy was developed in 1993 [159] and brought into clinical practice by Martin Walz [160]. This approach has gained popularity because it offers advantages, including direct access to the gland and the option of bilateral adrenalectomy without a requirement for repositioning if a prone approach is used.…”
Section: Surgerymentioning
confidence: 99%